Sacred Rivals Catholic Missions and the Making of Islam in Nineteenth-Century France and Algeria - Peterson, Joseph W. (Oxford University Press, 2022)
France;Algeria;Ottoman Syria;Islam;Catholicism;Catholic Orientalism;Imperialism;Missions;Jesuits;Louis Veuillot;Melchior de Vogüé;Charles Lavigerie;White Fathers;Humanitarianism;Œuvre d'Orient;Civilizing Mission